PEMEKARAN DAN PEMBANGUNAN INFRASRUKTUR DI KECAMATAN KOTO KAMPAR HULU (STUDI KASUS PEMVBANGUNAN INFRASTRUKTUR DI DESA TANJUNG TAHUN 2010-2013 - Rahmad Mel; Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Subdistrict Koto Kampar Hulu by the Regional Regulation No. 2 of 2010, this district is a division of the District XIII Koto Kampar, the purpose of this division course to accelerate development in the region. Special Desa Tanjung, which is the Capital District 's construction Hulu Koto Kampar more because of the facilities are located in rural districts such as, Head Office, Health Center, and the Grand Mosque . However, after 3 years of the status of the district, sub-district capital city is still a village, and based on observations while writer, infrastructure development in the Desa Tanjung as the Capital District is still lagging behind when compared to other districts with the capital.The purpose of this study was to determine the development of infrastructure in the Desa Tanjung after splitting districts Koto Kampar Hulu years 2010-2013 and to know Factors Affecting the Development of infrastructure in the village of Koto Kampar District of the Upper Cape 2010-2013. Theory (approach ) is used as an analytical tool in this study is the theory of Development and Proliferation. While the methods used in this research is descriptive qualitative research that is intended to provide a systematic overview of the observed phenomena.Based on these results , the District Redistricting no significant impact for Infrastructure Development in the Desa Tanjung, especially road infrastructure development has not changed (still broken since pre-expansion), yet the addition of clean water infrastructure to offset the increase in the consumption of the population, the absence of additional power lines entrance to the village since before the expansion, as well as the people who abandoned the market in the wake of the destruction of the access road to the site . Meanwhile, factors affecting the unavailability of infrastructure in the village of Tanjung after splitting districts, in other words, the expansion does not affect the development of infrastructure, among others, lack of government initiative in managing the affairs of the village households, lack Revenue Village ( PADes ), and Redistricting which tend to be forced.Keywords: Impact, Expansion, District, Desa Tanjung.